Narrativas de mistério e de suspense: propostas para a formação do leitor literário - LIMA, Elitânia Vieira (Universidade Federal do Tocantins, 2024)
This work focuses on the line of research “Reading and textual production: social diversity and teaching practices” and met the requirements of the Professional Master’s Program in Languages - Profletras, in carrying out an intervention activity with students. For this, we chose the literary reading contemplated in the literary genres short story, novella and novel, with the themes of mystery and thriller, as an object of study capable of contributing to the formation of the literary reader. In this study, we intend to show that it is possible to train readers at school with reading practices and through works mediated and supported by efficient methods. The research was developed with students from the 6th year of elementary school in a public school in the municipality of Buriticupu, in the state of Maranhão. So, it was necessary to find a method that was able to respond to the question: How can reading practices of mysteries and thriller stories contribute to the formation of the literary reader? To this end, Action Research and the qualitative approach proved to be more adequate to achieve the general objective, which aimed to analyze and problematize the implications of literary reading practices of mystery and thriller texts, without losing sight of competences and skills. Designed for this type of practice with the students in question. And so we chose the following works for this analysis: the novella by author Alexandre de Castro Gomes, “Who killed Saci?”; the novel by the authors Martin Widmark and Helena Willis, with the title "The mystery at school" and the short story by the author Flávio de Morais, in "The lesson of the skull". To use these literary genres, we follow the steps of the basic sequence of Cosson (2018), which proposes the following moments: Motivation, Introduction, Reading and Interpretation. As for the theoretical framework, we join the theories of Moisés (2001), Soares (2000), Cosson (2018), Graça Paulino (2004), Colomer (2007), and others. With this research, students immersed themselves in the literary universe, by reading and sharing the readings in the mediated process at the same time that we form a community of readers in the classroom, guaranteeing them the creation of links with literary reading, because their constant practice makes it possible to better understand the world of languages.